Development of athletic learning media for elementary school students - Da'i, Mohamad; Apriyanto, Rohmad; Ningsih, Wahyu; Mellati, Ita Khusnia (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
The problem that faced in athletic learning is the interesting and motivates of athletic learning media, for  students to learn has not been created, especially in the form of Android-based mobile learning. This research aims to develop the Smart Athletic App, and determine the feasibility of the product based on expert validation and usability factors. This type of research is Research and Development (R&D) which uses the ADDIE development model. The subjects of this research are 1 media expert, 1 material expert, and 22 class V students at SDN Sambiroto. The instrument used was aim to  measure product feasibility based on validation and usability factors. The results of this research obtained: (1) Creation of Athletic Smart Apps Products; (2) Feasibility has been well tested in terms of material, media, and usability factors in the "very feasible" category. Expert validation test results: (1) Material Expert of 4.47 is in the range > 4.0 as a result it is "very feasible" category; (2) The Media Expert Validation Score of 4.70 is in the range >4.0 thus dwtwemined "very feasible" category. The usability factor fromfeasibility test result of 6.24 is in the range > 5.5  "very feasible" category.